2019
DOI: 10.1002/jper.18-0464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic kidney disease on progression of clinical attachment loss in older adults: A 4‐year cohort study

Abstract: Background People with chronic kidney disease (CKD) may have an increased risk of periodontal disease, but longitudinal evidence is sparse. Methods This 4‐year cohort study assessed the association between CKD and changes in periodontal health status, defined by attachment loss (AL) progression, among older adults. Participants were 388 community‐dwelling Japanese adults who were 70 years old at baseline with 7053 teeth. Estimated glomerular filtration rate (eGFR) was calculated by using baseline serum creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Similar results were found in another study performed on rats, and therapeutic agents such as melatonin that can control oxidative stress were shown to limit these effects 12 . In a clinical study on an elderly population, Iwasaki et al showed that chronic kidney disease can increase periodontal destruction 10 . In a cohort study, Sharma et al 15 reported that the prevalence and severity of periodontitis were higher in patients with kidney disease.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Similar results were found in another study performed on rats, and therapeutic agents such as melatonin that can control oxidative stress were shown to limit these effects 12 . In a clinical study on an elderly population, Iwasaki et al showed that chronic kidney disease can increase periodontal destruction 10 . In a cohort study, Sharma et al 15 reported that the prevalence and severity of periodontitis were higher in patients with kidney disease.…”
Section: Introductionmentioning
confidence: 53%
“…Similarly, Zeng et al 26 reported that serum levels of creatinine, the most commonly used marker of glomerular filtration rate, was increased in the obese group, and a greater increase was observed in the obese group with periodontitis 26 . Similar to animal studies, in human studies, 10,52 periodontitis alone was shown to cause significant increases in these parameters and loss of kidney function. The results of experimental studies performed in obese rats have been inconsistent with clinical studies, 53–55 which may have been due to the periodontitis models used.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The dentist after navigating the impact of systemic disturbances on the periodontium will definitely find that usual scaling and root planning is only a relief but not a cure in many cases. Therefore, it is mandatory to detect and uncover the systemic disorders which aggravate gingival inflammation in order to provide a comprehensive and definite treatment [18]. In addition, when the dentist investigates the gingival and periodontal diseases as the first manifestation of many systemic disorders, great numbers of serious illnesses will be early diagnosed.…”
Section: Systemic Disturbances Which Can Cause Loss Of Periodontal Timentioning
confidence: 99%